2016
DOI: 10.13005/ojc/320205
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Global Reactivity Descriptors of some Newly Synthesized Unsymmetrical Sulfamides

Abstract: In the present study a series of unsymmetric linear sulfamides (1-9) starting from a primary amine were synthesized and their structures were confirmed by elemental analyses, mass spectrometry and 1 H NMR techniques. All the synthesized compounds were screened for their antibacterial activities by both disc diusion and minimal inhibition concentration (MIC) methods. Frontier molecular orbital (FMO) analysis and global reactivity descriptors have been performed using the density functional theory (DFT) with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The chemical potential (μ) was computed negative which indicated that this compound does not decompose spontaneously into the compounds from which it is made up of . The small value of hardness (η) and a large value of softness (S) indicated that the system is polarizable, which was further confirmed by the large value of computed dipole moment . These values together with small HOMO‐LUMO gap (ΔE) and negative binding energy confirmed that the title compound is polarizable and reactive in nature, hence could bind with DNA …”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The chemical potential (μ) was computed negative which indicated that this compound does not decompose spontaneously into the compounds from which it is made up of . The small value of hardness (η) and a large value of softness (S) indicated that the system is polarizable, which was further confirmed by the large value of computed dipole moment . These values together with small HOMO‐LUMO gap (ΔE) and negative binding energy confirmed that the title compound is polarizable and reactive in nature, hence could bind with DNA …”
Section: Resultsmentioning
confidence: 80%
“…Since a strong nucleophile is characterized by a lower value of chemical potential and electrophilicity index, the obtained values point towards the reactive nature of the title compound. The chemical potential (μ) was computed negative which indicated that this compound does not decompose spontaneously into the compounds from which it is made up of . The small value of hardness (η) and a large value of softness (S) indicated that the system is polarizable, which was further confirmed by the large value of computed dipole moment .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…On the other example, Bendjeddou et al (2016), sulfamides derivatives containing thiophene, pyridine, benzyl, and isopentyl alkyl end revealed that the majority of the synthesized compounds were fairly active against all tested bacteria. These compounds exhibited a broad spectrum of activity with inhibition zones values 13-36 mm against Enterobacteriaceae and S. aureus [30].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Sulfonamides form the foundation for the first drugs mainly employed as preventive and chemotherapeutic agents against different ailments. 10 Sulfa drugs, having sulfonamide functionality, revolutionized the medicinal field due to their extensive biological activities. 11 Folic acid, an important compound for synthesis of bacterial nucleic acids, is inhibited by sulfonamides which ultimately leads to death of bacterial cells.…”
Section: Introductionmentioning
confidence: 99%